Evaluating the effectiveness of interlocal government collaboration in planning and implementation of local road infrastructure the case of Palma-PB Alliance, North Cotabato, Philippines - Agatep, Pia May G. (School of Urban and Regional Planning, University of the Philippines Diliman, 2015)
Pursuant to Section 33 of the Code provides that "local government units may, through appropriate ordinances, group themselves, consolidate or coordinate their effort, services and resources for purpose commonly beneficial to them." Inter local cooperation among local government units are seen as intruments for local governments to increase their ability to carry out their mandates under decentralization. This has been observed in PALMA PB Alliance, in what was dubbed as the Kabalikat PALMA infrastructure Project, the member LGUs of the PALMA alliance pooled their infrastructure equipment, machinery, personnel and expertise to collectively work on road building projects in the member LGUs. Hence, PALMA PB Alliance in the Province of North Cotabato was selected as the area for this research work. The main objective of this research work is to understand how effective interlocal government collaborations are in terms of planning, implementing and financing infrastructure development in the local government units through criteria. These criteria include efficiency, equity, accessibility and accountability, and local responsiveness. In this regard, data collection tools employed in the study are are key informant interview/survey, existing documents from and pertaining to the PALMA PB alliance, focused group discussion with different stakeholders and organizations involved in the alliance for discussion and validation of preliminary results and findings and review of previous research accounts (theses, publications and books). To analyse data gathered, the researcher processed from sthe key informant interview/survey, performed content analysis of the existing documents and cross analysis of the perceived, stated and revealed results. Lack of available information and documentation and time constraints were the main limitations of the study. From the results of the evaluation through the enumerated criteria above, interlocal collaborations are indeed an effective scheme for planning, implementing and financing local road infrastructure projects. Beyond the evaluation based on the criteria, study was also able to answer specific questions on the benefits, impacts, critical factors that sustain the alliance and lessons learned in the alliance. Finally, the experience and process presented in the study can contribute as a resource material for further studies on the implementation on inter-LGU collaborations to plan, implement and finance local infrastructure development. The study will provide wider appreciation and understanding of the innovative ways and means of planning & engaging several LGUs collectively to form an alliance. Nevertheless, further studies may be conducted to provide an improved operational framework based on the findings of this and the succeeding research studies on this topic.